Predictors of Advance Care Planning Documentation in Patients With Underlying Chronic Illness Who Died of Traumatic Injury - Kim, Justin; Engelberg, Ruth A.; Downey, Lois; Lee, Robert Y.; Powelson, Elisabeth; Sibley, James; Lober, William B.; Curtis, J. Randall; Khandelwal, Nita (Journal of pain and symptom management, 2019)
Advance care planning (ACP) is difficult in the setting of a life-threatening trauma but may be equally important in this context, especially with increasing numbers of trauma victims being elderly or having multimorbidity. Identify predictors of absent ACP documentation in the electronic health records of patients with underlying chronic illness who died of traumatic injury. We used death records and electronic health records to identify decedents with chronic life-limiting illness who died of traumatic injury between 2010 and 2015 and to evaluate factors associated with documentation of living wills, durable powers of attorney, or physician orders for life-sustaining treatment. Only 22% of decedents had ACP documentation at time of injury. Among those without preinjury ACP documentation, 4% completed ACP documentation after injury. In multipredictor analyses, patients were less likely to have ACP documentation at the time of injury if they were younger (P < 0.001), had fewer chronic illnesses (P = 0.002), and had fewer nonsurgical hospitalizations (P = 0.042) in the year before injury. Among patients without ACP documentation before injury, those with fewer postinjury nonsurgical hospitalizations were less likely to complete ACP documentation after injury (P = 0.019). Our findings suggest that patient characteristics play an important role in the completion of ACP among patients with chronic life-limiting illness and who died from sudden severe injury. Interventions to improve ACP completion by patients with serious chronic conditions have the potential for increasing goal-concordant care in the event of traumatic injury.